Community Service for Grade IV Elementary Schools by Implementing Healthy Snacks at Cipunagara Public Elementary School - Evi Sonjati; Anis Nugraha; Annisa Nur Safitri; Vena Anggiyani; Moch. Fauzie Rahman S (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
Snack food is food and drink that is processed by food artisans at the point of sale and or served as ready-to-eat food for sale to the public other than those served by catering services, restaurants or restaurants and hotels. Government (PP) No. 19 of 2005 concerning National Education Standards (SNP) that every education unit is required to have facilities and infrastructure, including a canteen or school canteen. Based on the results of the BPOM survey, it shows that 99% of school children buy snacks at school. Healthy and nutritious snacks are very important in playing a role in providing energy and nutrition for children, especially school age. Along with the times, more and more chemicals have been developed and used as additives in snacks and food. Poisoning cases in Indonesia from 2004 until now are still a polemic from the mass media, electronic media. are poisoning due to snack food and processed food poisoning. The purpose of the research is to socialize in increasing knowledge and changing the behavior of female students so they understand healthy snacks. The method used in this research is descriptive research method. This activity is carried out in the form of counseling by displaying material in the form of power points, posters, videos. The sample is 25 class IV students and students. Data collection techniques were carried out by interviews, observation, and documentation. The results show that 60% of students with a lack of knowledge still eat snacks carelessly at school without sorting out healthy or unhealthy foods, for example, snack drinks that contain striking dyes, fried foods that come from black oil. 20% snacks at school and supplies at home, 10% of students don't snack carelessly.